Ezrin/Radixin/Moesin Proteins and Flotillins Cooperate to Promote Uropod Formation in T Cells - Martinelli, Sibylla; Chen, Emily J.; Clarke, Fiona; Lyck, Ruth; Affentranger, Sarah; Burkhardt, Janis K.; Niggli, Verena (Frontiers in Immunology, 2013)
T cell uropods are enriched in specific proteins including adhesion receptors such as P-selectin glycoprotein ligand-1 (PSGL-1), lipid raft-associated proteins such as flotillins and ezrin/radixin/moesin (ERM) proteins which associate with cholesterol-rich raft domains and anchor adhesion receptors to the actin cytoskeleton. Using dominant mutants and siRNA technology we have tested the interactions among these proteins and their role in shaping the T cell uropod. Expression of wild type (WT) ezrin-EGFP failed to affect the morphology of human T cells or chemokine-induced uropod recruitment of PSGL-1 and flotillin-1 and -2. In contrast, expression of constitutively active T567D ezrin-EGFP induced a motile, polarized phenotype in some of the transfected T cells, even in the absence of chemokine. These cells featured F-actin-rich ruffles in the front and uropod enrichment of PSGL-1 and flotillins. T567D ezrin-EGFP was itself strongly enriched in the rear of the polarized T cells. Uropod formation induced by T567D ezrin-EGFP was actin-dependent as it was attenuated by inhibition of Rho-kinase or myosin II, and abolished by disruption of actin filaments. While expression of constitutively active ezrin enhanced cell polarity, expression of a dominant-negative deletion mutant of ezrin, 1–310 ezrin-EGFP, markedly reduced uropod formation induced by the chemokine SDF-1, T cell front-tail polarity, and capping of PSGL-1 and flotillins. Transfection of T cells with WT or T567D ezrin did not affect chemokine-mediated chemotaxis whereas 1–310 ezrin significantly impaired spontaneous 2D migration and chemotaxis. siRNA-mediated downregulation of flotillins in murine T cells attenuated moesin capping and uropod formation, indicating that ERM proteins and flotillins cooperate in uropod formation. In summary, our results indicate that activated ERM proteins function together with flotillins to promote efficient chemotaxis of T cells by structuring the uropod of migrating T cells.